2018
DOI: 10.1029/2018jb015868
|View full text |Cite
|
Sign up to set email alerts
|

Structural Control on Downdip Locking Extent of the Himalayan Megathrust

Abstract: Geologic reconstructions of the Main Himalayan Thrust in Nepal show a laterally extensive midcrustal ramp, hypothesized to form the downdip boundary of interseismic locking. Using a recent compilation of interseismic GPS velocities and a simplified model of fault coupling, we estimate the width of coupling across Nepal using a series of two‐dimensional transects. We find that the downdip width of fault coupling increases smoothly from 70 to 90 km in eastern Nepal to 100–110 km in central Nepal, then narrows ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 93 publications
(223 reference statements)
7
54
0
Order By: Relevance
“…Comprehensive analysis of interseismic deformation indicates that the crustal ramp is an active structure beneath the topographic front of the Higher Himalaya (Berger et al, ; Grandin et al, ; Lindsey et al, ). The ramp seems spatially coincident with the clustered background microseismicity (Pandey et al, ), indicating that high shear stress is building up near such geometrical variation under steady tectonic loading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive analysis of interseismic deformation indicates that the crustal ramp is an active structure beneath the topographic front of the Higher Himalaya (Berger et al, ; Grandin et al, ; Lindsey et al, ). The ramp seems spatially coincident with the clustered background microseismicity (Pandey et al, ), indicating that high shear stress is building up near such geometrical variation under steady tectonic loading.…”
Section: Discussionmentioning
confidence: 99%
“…Previous earthquakes in this region exhibited similar behavior, leading to the hypothesis that shallow portion of the megathrust may act as strain reservoir, with elastic energy tranferred and stored from deep, more frequent but smaller ruptures until a great earthquake eventually sweeps through these shallow regions (Bilham et al, 2017). These observations suggest that downdip seismogenic segmentation of the MHT is geometrically controlled (e.g., Qiu et al, 2016;Lindsey et al, 2018), as has been suggested in other regions (e.g., Bletery et al, 2016;Duan, 2012;Yang et al, 2013). However, slip distributions of the Gorkha earthquake mimic incomplete ruptures in other regions where incomplete rupture seem to be depth-controlled, which is consitent with the notion that a plate boundary thrust is zoned according to frictional strength variations (e.g., Konca et al, 2008;Perfettini et al, 2010;Lay et al, 2012;Moreno et al, 2018).…”
Section: Introductionmentioning
confidence: 89%
“…To assess the extent of interseismic coupling, we use an updated set of GPS-derived velocities spanning the 1990s to 2015 (Kreemer et al, 2014). This data set was recently used to estimate the width of coupling across the MHT through a series of two-dimensional transects (Lindsey et al, 2018) (supporting information, Figure S1). To better resolve the pattern of coupling we also include leveling measurements from the Survey of Nepal collected between 1977 and 1990 (Jackson & Bilham, 1994).…”
Section: Geodetic Observationsmentioning
confidence: 99%
“…Previous studies have mentioned that resolving the detailed geometry of the plate boundary is important for assessing the size and location of future megathrust earthquakes (e.g., Hubbard et al, 2016;Qiu et al, 2016). Lindsey et al (2018) connect control of the transition from locked to creeping to the midcrustal ramp in central Nepal. Our results suggest that a heterogeneous crustal structure around the plate boundary may be associated with changes in fault slip behavior, including control on the extent of updip rupture and variations in coseismic slip and seismicity.…”
Section: Discussionmentioning
confidence: 99%